(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The study identified three main types of translation (without taking into account the grammatical structure of the paremiological unit): 1 type (method) - the proverbs coincide completely both in meaning and in lexical structure; 2 type (method) - the proverbs fully coincide in their meaning and do not coincide in their lexical structure; 3 type (method) - proverbs partially coincide in their meaning and completely do not match the lexical structure. The methods of translation are ranked according to the degree of their productivity. The most productive method is the second, the least productive is the first. The study showed that for practically all Belarusian proverbs can be found English equivalents that will completely or partially coincide in their content plan and will coincide or diverge in their form plan. The coincidence of proverbs in their content and the differences in proverbial realities and images are proved by the fact that proverbs in Belarusian and English reflect universal or isomorphic types of situations, have a close logical content, but they differ in their images and realities with the help of which the same or close paremiological meaning is conveyed. While selecting an analogue in the target language, it is important to take into account the semantic and stylistic features of proverbs, as well as the presence or absence of national peculiarities in proverbs. The national peculiarities can be determined both by the specific marking of the single proverbial component, and by the whole paremiological unit, connected with the national characteristics of its people. Besides, the interpreter must know the meaning of the proverb in the target language, which would exactly correspond to the situation or context. The author of the article together with E. Ivanov compiled the Belarusian-English paremiological dictionary, in which 605 English proverbs were selected for 175 Belarusian proverbs.